Intimations amid Intimidations: Singleness and Transcendence in Wordsworth's "Ode". Issue 2 (1st October 2022) - Larkin, Peter
Abstract : This article considers a factor of intimidation underlying the "intimations" of Wordsworth's "Ode" without belying the intuitions of the poem. The poet's contrast between childhood illumination and adult alienation produces intimidating forms of resistance and complexity which are also cues towards further poetic exploration. This process centres on the ambivalent ontology of a "field of many one" and a "single field, " at once sites of spiritual deficit and a mysterious reserve of "things" simply remaining what (if not always as) they are. The article distinguishes the "single" from the "singular" with a glance at two postmodern commentators and investigates the perceptual relations of mind and world explored in Merleau-Ponty, J. L. Chrétien and John Milbank. I conclude that Wordsworth's "Ode" doesn't provide a solution to the dilemma it raises but re-offers its own fears, hesitations, and recallings to an horizon of faith, one schooled by the promise of gift stubbornly mediated by single things.